Qualities of goat semen in Tris-Citrate-Glucose extender containing glutathione (Bangladesh Veterinarian, 2011)
Glutathione (GSH) 0 (control), 2, 4 and 8 mM was used in the preservation of chilled goat semen. Treated and control samples were kept at 4 – 5°C up to seven days. Sperm motility and acrosome abnormality were assessed daily under phase contrast microscope. The sperm motility was significantly (P